A Study on Consumer Opinion Towards Recycled Eco-Friendly Paper Products In Kerala - Biju M. K. and Vinod S. (Asian Journal of Research in Business Economics and Management, 2013)
This study is aimed at consumer opinion towards the recycled eco-friendly paper products in Kerala. Recycled Paper is the paper that has 30 percent post-consumer content with or without pre-consumer waste. It is important to know the consumer opinion on recycled paper and in turn communicate the need for moving to recycled paper from virgin paper. It is a social obligation to everyone in the society. The study used primary data collected through a questionnaire survey. Convenient sampling was adopted and the sample size was 100. Percentages, Likert scale and statistical test were used for the analysis of data. The analysis shows that the consumers are satisfied with the attributes of recycled paper and they are not highly satisfied. The test shows that there is no difference in opinion of different category of consumers on recycled paper.